Estudio fotofísico y fotoquímico de complejos de Re(i) mediante las técnicas de laser flash fotólisis y radiólisis de pulso - Ragone, Fabricio (2013)
Re(I)tricarbonyl complexes of the type fac-XRe(CO)3L (where X= halide and/or substituted azine and L=a-diimine and fac indicates that the three carbonyls are on the same face of the octahedron) show exceptionally rich excited-state behavior and redox chemistry as well as thermal and photochemical stability. They have also been used as biological labeling reagents and noncovalent probes for biomolecules and ions. Moreover, there are potential biochemical and technical applications based on the formation of adducts between transition metal complexes of Re(I), and biological macromolecules such as DNA. In this work we present the synthesis and characterization of a new compound Re(CO)3(pterin)(H2O) (pterin 2-amine-4-oxo-3H-pteridine) (RePtas well as studies about the character, dynamics and reactivity of ground and excited states generated by irradiating solutions.